Educational interpreting: A dynamic role model - Kotzé, Herculene (Stellenbosch Papers in Linguistics Plus, 2014)
This article aims to describe the challenges faced by educational interpreters within a professional context with regard to role fulfilment and existing role models. This will be carried out by exploring the notions of ‘roles’ and ‘norms’ within Translation Studies (which includes interpreting) and investigating how these relate to and influence educational interpreting. The article will offer findings emanating from an extensive study and, by adopting a normative approach, provide an adapted role model specifically designed for educational interpreting.